Structural and Capacity Improvement of Polypropylene Disposable Food Containers Using FEA Software - Yon Ismail, Yon Izmelisa Adha; Muhammad A’imullah Abdullah; Khairu Kamaruddin (Progress in Engineering Application and Technology, 2025)
This study investigates the structural and capacity enhancement of polypropylene disposable foof containers through Finite Element Analysis (FEA) USING SolidWorks 2023, focusing on curves size enlargement. The original 4mm curve design was modified to 5mm and 6mm to address issues of structural instability and food waste cause by trapped residues. Simulations demonstrated that increasing the curve size significantly improve stress distribution and reduced displacement under various load conditions. The 6mm design shows incredible structural stability, usability and material efficiency, with the stress value remaining within safe limits for polypropylene. Prototypes were fabricated using PLA 3D printing for practical ‘first try’, while the final product is intended for injection molding with polypropylene to ensure food safety and durability. This research concludes that optimizing curve parameters enhances container performance, reduces food waste and supports cost-effective manufacturing, with the 6mm design emerging as the most viable solution.